A Worldwide Overview of Facts and Figures - Pallares-Miralles, Montserrat; Romero, Carolina; Whitehouse, Edward (World Bank, Washington, DC, 2012)
This paper presents and explains cross country data for mandatory publicly and privately managed pension systems around the world. Relevant World Bank demographic projections and other indicators previously reported in International Patterns of Pension Provision (2000) are updated, and relationships between key indicators are highlighted. For more than a decade, the World Bank has compiled and maintained a database on pension systems around the world. The process of collecting data began in the early 1990s when the Bank's first major research volume on the subject was published. Subsequently, expanding World Bank lending and technical assistance on pensions resulted in the collection of additional information, particularly in Eastern Europe and Latin America. In addition to providing more recent data, this update includes new and standardized information on system parameters. The aim of this document is to capture much of the relevant cross-country information and indicators. This is intended to provide decision makers with a general view of the current patterns of pension provision worldwide to support their efforts to develop well-informed frameworks for implementing and/or reforming pension systems.